Improving Power Quality in High-Rise Buildings with a Single-Tone Passive Filter and Capacitor Bank - Kasbi, Ahmad Aminul; Ruliyanta, Ruliyanta; Keraf, Adhyathta (Universitas Ahmad Dahlan, 2024)
Total harmonic distortion and a low power factor are critical issues affecting power quality in modern high-rise buildings. Non-linear loads generated by highly efficient electrical equipment cause total harmonic distortion. On the other hand, low power factor is caused by induction machines, excessively long cables, and inefficient equipment. This research aims to design a single-tunable filter and capacitor bank to address power quality issues. Our method involves utilizing a single-line building design diagram and conducting load simulations using ETAP 19.0.1 software. Our method is a harmonic load flow analysis. We use this method to calculate the harmonic distribution at various points within the electrical network. Harmonic flow analysis aids in identifying the harmonic contributions from various non-linear loads within the system. For research, we implemented a single-tuned passive filter and capacitor bank in the building's electrical system. We initiate the study by analyzing the transformer's total harmonic distortion (THD) and then make iterative adjustments to parameter values until we achieve compliance with the IEEE 519-2014 standard. As a result, the study recommends the installation of two single-tuned filters for orders 5 and 7, as well as the inclusion of a capacitor bank with a capacity of XXX. This reduces the system's THDi value from 21.77% to 4.45% and 22.63% to 4.45%, respectively. The power factor increased from 85.78% to 99.69% and 88.68% to 99.41%, respectively.